2018
DOI: 10.1111/risa.13254
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Planning in Agriculture: How Planning on Dairy Farms in Ireland Is Affected by Farmers’ Regulatory Focus

Abstract: This article examines how planning on dairy farms is affected by farmers' motivation. It argues that farmers' choice of expansion strategies can be specified in terms of risk decision making and understood as either prevention-focused or promotion-focused motivation. This relationship was empirically examined using mediated regression analyses where promotion/prevention focus was the independent variable and its effect on total milk production via planned expansion strategies was examined. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Besides that, no matter how robust the supply chain is, risks and uncertainties cannot be ruled out and require attention; if unattended, they will affect the supply chain adversely in many ways (Simchi-Levi et al , 2008). On risk in the supply chain, we can find the research conducted by Mishra and Shekhar (2011), Nasir et al (2014), Zubair and Mufti (2015), Daud et al (2015), Liu and Arthanari (2016), Chari and Ngcamu (2017), Prakash et al (2017) and Garvey et al (2018).…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides that, no matter how robust the supply chain is, risks and uncertainties cannot be ruled out and require attention; if unattended, they will affect the supply chain adversely in many ways (Simchi-Levi et al , 2008). On risk in the supply chain, we can find the research conducted by Mishra and Shekhar (2011), Nasir et al (2014), Zubair and Mufti (2015), Daud et al (2015), Liu and Arthanari (2016), Chari and Ngcamu (2017), Prakash et al (2017) and Garvey et al (2018).…”
Section: Literature Reviewmentioning
confidence: 98%
“…In this case, Ghosh et al (2014) found that training facilities and education programmes for staff and dairy farmers are two important risks to mitigate, whereas Prakash et al (2017) found that the supplier side, market risks, and process risks are three important risks to mitigate. Garvey et al (2018) did not list all of the risks in the dairy supply chain. Using regression analysis, they tried to test the relationship between the promotion or prevention focus strategy, which is indicated by the risk of decision making (independent variable), planned expansion strategies (intervening variables) and total milk production (dependent variable).…”
Section: Literature Reviewmentioning
confidence: 99%